2021
DOI: 10.3389/fmicb.2021.739319
|View full text |Cite
|
Sign up to set email alerts
|

Phage Selective Pressure Reduces Virulence of Hypervirulent Klebsiella pneumoniae Through Mutation of the wzc Gene

Abstract: Hypervirulent Klebsiella pneumoniae (hvKp), one of the major community-acquired pathogens, can cause invasive infections such as liver abscess. In recent years, bacteriophages have been used in the treatment of K. pneumoniae, but the characteristics of the phage-resistant bacteria produced in the process of phage therapy need to be evaluated. In this study, two Podoviridae phages, hvKpP1 and hvKpP2, were isolated and characterized. In vitro and in vivo experiments demonstrated that the virulence of the resista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 58 publications
1
23
0
Order By: Relevance
“…However, we hypothesise that similar results could be obtained with other phages that target A. baumannii ’s capsule, thus inducing capsule loss upon emergence of phage-resistance. It could even be possible for similar phenomena to emerge with other capsulated pathogens, as suggested by preliminary observations in Klebsiella pneumoniae 65 and Pseudomonas aeruginosa . 66 A final caveat regarding phage øFG02 is that, despite multiple attempts, 33 its genome remains unsequenced.…”
Section: Discussionmentioning
confidence: 77%
“…However, we hypothesise that similar results could be obtained with other phages that target A. baumannii ’s capsule, thus inducing capsule loss upon emergence of phage-resistance. It could even be possible for similar phenomena to emerge with other capsulated pathogens, as suggested by preliminary observations in Klebsiella pneumoniae 65 and Pseudomonas aeruginosa . 66 A final caveat regarding phage øFG02 is that, despite multiple attempts, 33 its genome remains unsequenced.…”
Section: Discussionmentioning
confidence: 77%
“…In phage-host interactions, modification/masking of bacterial surface receptors to evolve constitutive defenses against phages is often associated with fitness costs ( 20 , 34 37 ). To our knowledge, the type of fitness cost is mainly determined by the receptor type of the host, such as OMPs or LPSs.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study reported that mutations in genes essential for capsule biosynthesis in Acinetobacter baumannii confer resistance to phage adsorption through capsule loss ( 28 ). Similarly, the wcaJ gene is related to phage sensitivity ( 29 ), and its absence might protect isolates, particularly CR-hvKP, from lytic phage predation in vitro and in vivo ( 24 , 30 ), thus enhancing their viability.…”
Section: Discussionmentioning
confidence: 99%